2017
DOI: 10.1091/mbc.e17-02-0102
|View full text |Cite
|
Sign up to set email alerts
|

A cytoskeletal clutch mediates cellular force transmission in a soft, three-dimensional extracellular matrix

Abstract: Quantitative analysis of the pairwise dynamics of the actin cytoskeleton, focal adhesions, and ECM fibrils reveals how cytoskeletal dynamics drive matrix deformation and cell motility for primary human fibroblasts embedded in a 3D fibrin matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
63
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 92 publications
7
63
0
1
Order By: Relevance
“…In vivo, the nonlinearity of the elastic profile of the ECM is largely governed by degree of hydration and is dependent on the presence of cells as demonstrated by the almost perfectly elastic behavior of acellular, bulk ECM 12. Interestingly, cell‐derived strain‐stiffening of soft (≈200 Pa), fibrous ECM can result in an increase in the local stiffness sensed by neighboring cells, leading to a cell phenotype reminiscent of that observed on gels with E ≈50 kPa 13. These results are in agreement with additional studies that have shown cells seeded on soft, nonlinear elastic matrices show large cell areas (a hallmark of active mechanotransduction on stiff substrates) equivalent to those observed on stiff, linear elastic matrix 14,15.…”
Section: The Extracellular Matrix: Foundations Of Matrix Mechanics Ansupporting
confidence: 86%
See 1 more Smart Citation
“…In vivo, the nonlinearity of the elastic profile of the ECM is largely governed by degree of hydration and is dependent on the presence of cells as demonstrated by the almost perfectly elastic behavior of acellular, bulk ECM 12. Interestingly, cell‐derived strain‐stiffening of soft (≈200 Pa), fibrous ECM can result in an increase in the local stiffness sensed by neighboring cells, leading to a cell phenotype reminiscent of that observed on gels with E ≈50 kPa 13. These results are in agreement with additional studies that have shown cells seeded on soft, nonlinear elastic matrices show large cell areas (a hallmark of active mechanotransduction on stiff substrates) equivalent to those observed on stiff, linear elastic matrix 14,15.…”
Section: The Extracellular Matrix: Foundations Of Matrix Mechanics Ansupporting
confidence: 86%
“…Recently, there have been growing efforts to extend the observations reported in 2D clutch models to 3D systems. Though still largely unexplored, preliminary studies have revealed that a second cytoskeletal clutch may exist in the 3D environment that cooperates with the previously mentioned 2D clutch system to elongate stress fibers anchored at FAs, providing migrating cells a mechanism of maintaining consistent attachment to ECM throughout locomotion 13. Further studies that continue to expand 2D clutch observations into three‐dimensions will likely lead to exciting discoveries that extend current understandings of the molecular clutch to in vivo processes.…”
Section: The Extracellular Matrix: Foundations Of Matrix Mechanics Anmentioning
confidence: 99%
“…As such, retrograde flow inversely correlates with cell migration speed . The flow is partially transmitted to adaptor proteins and integrins, meaning molecules closer to the ECM experience progressively slower retrograde speeds . Retrograde flow is observed for different types of actin structures, from lamellipodia to stress fibers, and similarly in cadherin‐based cell–cell adhesions .…”
Section: Mechanotransduction At the Cell–matrix Interfacementioning
confidence: 99%
“…Drawing on previous work (Simson et al, 1998), we experimentally decreased apical surface bending energy with a cocktail of inhibitors (1 µM latrunculin A, 20 µM ML-7, 20 µM Y-27632, and 50 µM nocodazole) that works to acutely ablate the actomyosin and microtubule cytoskeletons (Owen et al, 2017) (Supplementary Video 1). Remarkably, lumen face shapes were largely unaffected by cytoskeletal ablation (Fig.…”
Section: Cells Regulate Both Luminal Pressure and Surface Area To Defmentioning
confidence: 99%